1998
DOI: 10.1093/humrep/13.3.604
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of angiotensin-converting enzyme in ejaculated human spermatozoa

Abstract: Angiotensin-converting enzyme (ACE) is known to be released from human spermatozoa during capacitation. However, it has not yet been localized ultrastructurally in ejaculated sperm cells. Therefore, the purpose of the present study was to demonstrate the location of ACE by means of immunoelectron microscopy and direct immunofluorescence. In addition, ACE activity of spermatozoa was correlated with standard semen parameters. The activity of angiotensin-converting enzyme was measured in spermatozoa from 115 dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
48
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 32 publications
4
48
1
Order By: Relevance
“…The levels of ACE on the surface of spermatozoa have been shown to be inversely proportional to their fertilization capacity (Kohn et al 1998, Shibahara et al 2001. Therefore, the increase in ACE levels in frozen-thawed spermatozoa may reasonably explain the problem of low fertility rate.…”
Section: Proteins Related To Premature Capacitationmentioning
confidence: 99%
“…The levels of ACE on the surface of spermatozoa have been shown to be inversely proportional to their fertilization capacity (Kohn et al 1998, Shibahara et al 2001. Therefore, the increase in ACE levels in frozen-thawed spermatozoa may reasonably explain the problem of low fertility rate.…”
Section: Proteins Related To Premature Capacitationmentioning
confidence: 99%
“…Previous studies revealed no relationships between the concentration/morphological characteristics of spermatozoa and ACE activity [7]. A positive correlation was revealed between ACE activity and motility of human and bovine spermatozoa [6].…”
mentioning
confidence: 67%
“…ACE gene knockout mice do not differ from intact animals by the number, motility, and morphological characteristics of spermatozoa. However, these cells are unable to pass through female genital tract and fertilize the oocyte [8,9].Previous studies revealed no relationships between the concentration/morphological characteristics of spermatozoa and ACE activity [7]. A positive correlation was revealed between ACE activity and motility of human and bovine spermatozoa [6].…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Accession number (a) Spermatozoa surface references 14-3-3 protein zeta chain YWHAZ 253706 Aconitase ACO1 5821963 Acrosin ACR 164703 [Mori et al 1995;Suter and Habenicht 1998] Aldose reductase ALDR2 8569627 [Kobayashi et al 2002;Frenette et al 2003] Alpha enolase ENO1 2661039 [Gitlits et al 2000] Alpha-mannosidase MAN2C1 1017779 [Okamura et al 1995;Pereira et al 1998;Kuno et al 2000] Angiotensin-converting enzyme ACE 145279215 [Kohn et al 1998;Gatti, et al 1999;Nikolaeva et al 2006 Zona pellucida-binding protein 1 ZPBP 47523020 [Yu et al 2006;Mori, et al 1995] a) Accession code for the identification in NCBI database…”
mentioning
confidence: 99%